2003
DOI: 10.21273/jashs.128.1.0128
|View full text |Cite
|
Sign up to set email alerts
|

Drought Effects on Green Pea Texture and Related Physical-Chemical Properties at Comparable Maturity

Abstract: Yield and seed texture were studied in green peas (Pisum sativum L.) subjected to drought stress during flowering and pod filling. Field experiments were conducted with two cultivars on a sandy loam soil and drought conditions were obtained using movable rain shelters. The plants were harvested at three to five stages of maturity determined by tenderometer values and the concentration of alcohol-insoluble solids (AIS). Measured variables were related to the concentration of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…These mechanisms include detoxification enzymes, redox status regulation, signaling pathways, protein folding and degradation, photosynthesis stability, and primary metabolism [18]. In addition, drought and low water content reduction lead to an increase in sugar and amino acid concentrations in plants [28].…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms include detoxification enzymes, redox status regulation, signaling pathways, protein folding and degradation, photosynthesis stability, and primary metabolism [18]. In addition, drought and low water content reduction lead to an increase in sugar and amino acid concentrations in plants [28].…”
Section: Introductionmentioning
confidence: 99%
“…However, both male and female reproductive organs are adversely affected by high temperatures, and floral organs are also vulnerable to heat stress before pollination and in the post-pollination stage [47]. Adequate moisture levels are also required during this period, as pea sensitivity to water deficiency increases during flowering and seed filling due to high evapotranspiration [48,49]. It is also noteworthy that the climatic conditions in May and June in the Rostov region are also significant factors in determining the yield of other crops.…”
Section: Discussionmentioning
confidence: 99%
“…In general, peas are more sensitive to water deficit during of flowering and pods/grains filling than is the vegetation stage (Lecoeur and Guilioni, 2010;and Rasaei et al, 2012). Sorensen et al (2003) reported that although the yield of green peas was affected by the drought stress but the texture quality could be maintained if green peas were harvested at the optimum maturity.…”
Section: Introductionmentioning
confidence: 99%